Comparative Study of Platelet Indices in Normal Pregnant and Non-Pregnant Women in a Tertiary Care Hospital in Northern India - Raychaudhuri, Sujata; Sharma, Nimisha; Arora, Sheetal; Pujani, Mukta; Rana, Deepsikha; Lukhmana, Shveta (Annals of Pathology and Laboratory Medicine, 2018)
Aims and Objectives: To compare Platelet Indices between pregnant females and non-pregnant females attending the Antenatal Clinic in a tertiary care hospital. Platelet Indices amongst pregnant women between the three trimesters were also compared. Materials and Methods: A case control study was conducted in the Department of Pathology, ESIC Medical College and Hospital, Faridabad, Haryana India on 119 normal pregnant females and 119 non-pregnant normal females in the reproductive age group (18 to 45 years) with the approval of the ethical committee. Venous blood was collected from all participants in EDTA vacutainer and CBC was performed using fully automated analyser, XN 1000 within 2 hours of sample collection. The data were analysed using SPSS software 17.0. Unpaired Student t-test was applied to compare the various platelet indices between the cases and controls. One-way ANOVA was applied to study between group differences among the three different trimesters of pregnancy for the platelet counts and indices. Results: Platelet count was found to be higher among controls as compared to cases and this was found to be statistically significant (p=0.017). Platelet count was highest among subjects in the first trimester and subsequently decreased among subjects in the second and third trimester. But was not statistically significant. An inverse relationship was seen between MPV and Platelet Count, this was statistically significant. Conclusion: The Platelet count and Indices were reduced in normal pregnancy. However, owing to a small sample size, the statistical significance of various platelet indices between cases and controls and among the three trimesters were limited.